Preventive Behaviors, Barriers, and Drivers of the COVID-19 Pandemic in Malaysia: A Cross-sectional Survey - Normaliza Binti Ab Malik; Rusyda Helma Mohd; Nor Ba’yah Abdul Kadir (Universitas Indonesia, 2024)
Indexed by WOS